Efficient immobilization of α-naphtyl acetate esterase (ANAE) on modified k-carrageenan, and k-carrageenan/alginate composite matrices – a comparative evaluation - Jameel, Ahmad Tariq; Abdul Jalil, Nur Syuhada (Elsevier, 2018)
Enzymes are protein that act as a catalyst to stimulate the biochemical reactions. By reducing the activation energy. However, free enzyme is expensive, unstable, difficult to separate and reuse thus limiting its applications in large-scale operations. Immobilization means confinement of enzymes usually in a semi-permeable matrix support to improve enzyme stability with respect to catalytic activity for repetitive use with the obvious ease of separation. This greatly increases the enzyme efficiency thus reducing the production cost in bioprocess industries. In this study, modified biopolymer such as cross linked pure k-carrageenan and k-carrageenan/alginate composite matrices are prepared as support for the immobilization of -naphtyl acetate esterase (ANAE) extracted from wheat flour. FESEM and FTIR spectroscopy characterization was done for the novel support matrices. Optimum key parameters were identified for immobilization yield and enzymatic activity for two immobilization methods of entrapment and covalent bonding for the two novel support matrices developed. Maximum immobilization yield of about 90% of ANAE on k-carrageenan/alginate composite matrix using covalent bonding was obtained for 3% polyelectrolyte polyethylene imine (PEI) solution, 4 h curing time and pH 8. For entrapment method, the maximum immobilization yield obtained was 89% for 5 h curing time. The maximum enzyme activity was observed for the physically entrapped ANAE on composite matrix support compared to free and immobilized enzyme on other matrices. Optimum pH and temperature was found to be around 8 and 42 ◦C respectively for the composite matrix. Reuseability appeared superior for covalently immobilized enzyme while storage stability was better for entrapment method.